Antibacterial, cytotoxic and genotoxic effects of nano-hydroxyapatite-silica glass ionomer cement and its dentine pulp complex response in a rat model - Niazi, Fayez Hussain (2025)
The aim of this study was to assess antibacterial and genotoxic effects of nano-hydroxyapatite-silica glass ionomer cement (nano-HA-SiO2-GIC) and its dentine pulp complex reactions’ evaluation in an animal model. Minimal bacterial concentration (MBC), minimal inhibitory concentration (MIC), and time kill assay (TKA) were carried out to assess antibacterial efficacy for 10% nano-HA-SiO2-GIC and compared with conventional Glass ionomer cement (cGIC) against three different bacteria Streptococcus mutans, Staphylococcus aureus and Enterococcus faecalis. Mutagenicity and DNA damage of nano-HA-SiO2-GIC using Comet assay and Ames test were also evaluated. Further, an in-vivo study was performed to evaluate and compare the dentin–pulp complex response following occlusal and cervical restorations in rat molars restored with nano-HA-SiO2-GIC and cGIC. It was found that both S. aureus and E. faecalis exhibited comparatively greater resistance to cGIC with an MIC of 30μg/mL. In contrast, the MIC of cGIC against S. mutans was 20μg/mL. The MIC for nano-HA-SiO₂-GIC were the same for E. faecalis when compared with cGIC (30μg/mL) whereas it was 10μg/mL for both S. mutans and S. aureus (p < 0.05). Time kill assays revealed that nano-HA-SiO₂-GIC effectively killed 99% of the tested bacteria after 6 hours whereas cGIC was able to eradicate these bacteria in 8 hours. The highest cell viability (159.4%) for nano-HA-SiO2-GIC was noticed at 3.125 mg/ml, while the lowest (24.26%) was observed at 200 mg per ml. IC50, IC25 and IC10 values were 95.27, 51.4 and 20.1 mg/ml for cGIC, and 106.9, 55.8 and 22.9 mg/ml for nano-HA-SiO2-GIC respectively. The IC10 of both test materials showed no significant DNA damage compared to that of the negative control based on the Comet assay (p > 0.05). Despite this, a significant difference was present in the tail moment between all concentrations of both types of GIC groups as well as the positive control (p < 0.05). Nano-HA-SiO2-GIC showed less than double the average number of revertant colonies compared to that of the negative control when tested using Ames test. For in-vivo studies, parameters such as disorganization of the pulp tissue, inflammatory cell infiltration, detection of bacteria, and tertiary dentin deposition were measured for each group. Overall, there was no difference between cervical and occlusal restorations in terms of remaining dentine thickness (RDT). One week after the sacrifice, the odontoblastic layer was disrupted the pulp area close to the cut dentin displayed moderate inflammation in both types of restorations. One month after sacrifice, there was no evidence of disruptions of the odontoblast layer. In terms of inflammation, the pulp tissue recovered in almost all cases except one of c-GIC, but a few cases of the nano-HA-SiO2-GIC group still displayed mild-to-moderate inflammatory reactions, especially on the occlusal restorations. A significant difference in tertiary dentin thickness (TDT) in first molars was observed for both cGIC (66.21 ± 43.15), and nano-HA-SiO2-GIC (96.66 ± 41.2) as compared to second molars (31.97 ± 5.30). The addition of nano-HA-SiO2 to cGIC significantly enhanced the antibacterial properties, found to be non-mutagenic and do not cause DNA damage at the lowest concentration of IC10 based on the Comet assay. In addition, it exerted favourable dentine pulp complex response when compared to cGIC. Based on the findings of the current study, nano-HA-SiO2-GIC produce promising findings and thus can be suggested as a future potential material for use in clinical dentistry